FRI0180 SURVEY ON HELP-SEEKING AND DISEASE TRAJECTORY IN SYSTEMIC LUPUS ERYTHEMATOSUS. (2nd June 2020) - Eguez del Pozo, M. F.; Micelli, M.; Cañizares Calderón, A.; Avila, P.; Fara, N.; Garcia Faura, L.; Alvarez, D.; Sequeira, G.; Kerzberg, E.
Abstract : Background: Few studies in Latin America have analysed the time lag since patients experience the first joint symptoms until they consult a physician, and a diagnosis is made, and most of them have dealt with patients sustaining Rheumatoid Arthritis (RA) 1-2 . Objectives: To study both patient and disease factors that have some bearing on the time lag until a physician is first consulted and a diagnosis is made. Methods: Multiple-choice survey to patients of 18 years of age or older who met Systemic Lupus Erythematosus (SLE ) Classification Criteria (2012). The following aspects were measured: time lag from symptom onset to first medical consultation (Time 1), time lag since first medical consultation until a diagnosis is made (Time 2), and time lag until the first consultation with a rheumatologist . Patients were interviewed at the time or within 6 months of diagnosis, and asked about the physician they first consulted and the one who made the diagnosis. They were also requested to describe one disease onset out of 4 trajectories: acute, acute with temporary remissions, chronic with partial improvements, or sustained chronic. Patients were required to recount their response to the first symptoms, the limitations brought about by the disease (employing the Steinbrocker scale), and whether help-seeking was first aimed at consulting a physician or they decided to wait. A group of patients with Rheumatoid Arthritis (RA) answered the same survey. Every patient signed an informed consent form, and the study was approved by the Hospital Bioethics Committee. Results: Twenty-eight patients with SLE and 29 patients with RA filled in the survey. SLE patients were younger as expected (32 years vs 49 years; p <0.001). Acute was the most common disease trajectory in SLE patients (36% vs 34%; p 0.8) and chronic in RA (38% vs 32%; p 0.8). The first professional consulted was an on-duty physician in SLE (36% vs 24% in RA; p 0.5). Except for the matter of computer at home and/or a mobile phone with an Internet connection at home, both groups were similar, although SLE patients showed a trend to better level education and lesser impact of the disease on daily life at the beginning (see Table 1 ). Time 1 in patients with SLE was significantly lower with a median of 7 days, range (25-75%) 1-30 days vs 30 days in RA, range 14-180 (p 0.01), and the former also showed a trend to lower median Time 2: 81 days, range 25-209 vs 185 days in RA, range 60-275 (p 0.1). Besides, they showed a significantly shorter time lag until the first visit to a rheumatologist with a median of 120 days, range 35-225 vs 330 days, range 120-450 in patients with RA (p 0.005). Conclusion: SLE patients consult a physician and visit a rheumatologist sooner than RA patients do, and they also show a trend to obtain a faster diagnosis. Education, health insurance, employment, the disease impact on their daily life and initial response to the symptoms do not appear to account for their swiftness in seeking medical help. References: [1]Mussano E, Missakian S, Onetti CM (2007) Estudio demográficosocial de pacientes con artritis reumatoidea en la provincia de Córdoba (Argentina). Rev Argent Reumatol 4:13–22. [2]Rodríguez-Polanco E, Al Snih S, Kuo YF et al (2011) Lag time between onset of symptoms and diagnosis in Venezuelan patients with rheumatoid arthritis. Rheumatol Int 31:657–665. doi:10.1007/s00296-009-1358-9. Disclosure of Interests: None declared